Pemisahan Anomali Regional-Residual pada Metode Gravitasi Menggunakan Metode Moving Average, Polynomial dan Inversion - Jarot Purnomo; Sorja Koesuma; Mohtar Yunianto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
It has been done a research about separation of regional-residual anomaly in Gravity method. This research compares the result of three methods i.e. moving average method, polynomial method, and inversion method. The computer program is created using a computer programming Matlab 7. From three methods that have been made, the separation results are compared withresults of separation by using Upward Continuation method. From the results of these comparisons will be available an excellent program of regional-residual anomali separation. The results show that in polynomial method of the order 4 obtained similar contour to the separation by Upward Continuation Software. So that the output of this separation will be treated again with Grav2DC software. The output of this software is the density of rock Grav2DC of the studyarea. Processing results obtained the minimum error of 1.85% for the separation by polynomial method, while for the method of Upward Continuation obtained minimum error of 2.22%. The results obtained show that the separation of regional-residual anomali by polynomial method is similar to separation by Upward Continuation method.